A Numerical Investigation for a Model of the Solid-Gas Phase in a Crystal Growth Apparatus (Communications in Computational Physics, 2008)
We present discretization and solver methods for a model of the solid-gasphase in a crystal growth apparatus. The model equations are coupled Eulerian andheat-transfer equations with flux boundary conditions. For a more detailed discussionwe consider simpler equations and present time- and space-decomposition methods assolver methods to decouple the multi-physics processes. We present the error analysisfor the discretization and solver methods. Numerical experiments are performed forthe Eulerian and heat-transfer equation using decomposition methods. We presenta real-life application of a crystal growth apparatus, based on underlying stationaryheat conduction. Finally we discuss further error analysis and application to a morecomplex model of crystal growth.